The Contextual Effect of Social Norm on Early Marriage Among Young Women in Lampung: A Multilevel Analysis Evidence - Agtikasari, Nurhayati; Soemanto, RB.; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Early marriage